Sensitivity of some local isolates of Mycoplasma gallisepticum against antibiotics - Sutiastuti Wahyuwardani; Soeripto . (Indonesian Center for Animal Research and Development (ICARD), 1998)
Sensitivity of five local isolates ofMycoplasma gallisepticum (MG) strain and two standard MG isolates obtained from Australia were tested against antibiotics of oxytetracycline, doxycycline, erythromycin, bacitracin, vancomycin, methicillin and penicillin using antibiogram disc method. The result showed that one, 2 and 3 local MG isolates were resistent to doxycycline, erythromycin and oxytetracycline respectively . MG isolate of ADA7 from Australia was found to be resistent to all antibiotics tested. None ofthe local MG isolates were sensitive against bacitracin, vancomycin, methicillin and penicillin. Key words: Mycoplasma gallisepticum, antibiogram disc